Investigations to Hygroscopic Aerosol Growth Within the Convective Boundary Layer - Althausen Dietrich; Reigert Andrew; Wandinger Ulla; Reichardt Jens (EPJ Web of Conferences, 2020)
We present a new method to determine the hygroscopic growth of atmospheric particles. This method combines lidar measurements with high temporal resolution of the particle backscatter coefficient and water vapor mixing ratio with temperature measurements from radiosondes and a microwave radiometer. The hygroscopic growth is described by an equation that represents the two observed branches of the growth curve with different dependencies on the relative humidity. An example is presented to illustrate a first result from a continental air mass case.